A novel hydrogen peroxide sensor based on electrodeposited copper/cuprous oxide nanocomposites. Issue 2 (5th December 2018) - Han, Long; Tang, Li; Deng, Dongmei; He, Haibo; Zhou, Mi; Luo, Liqiang
Abstract : Copper/cuprous oxide nanocomposites were electrodeposited on a fluorine doped tin oxide (FTO) glass substrate for sensitive determination of hydrogen peroxide. Abstract : In this work, copper/cuprous oxide (Cu/Cu2 O) nanocomposites were electrodeposited on a fluorine doped tin oxide (FTO) glass substrate for sensitive determination of hydrogen peroxide (H2 O2 ). The Cu/Cu2 O nanocomposites were synthesized on FTO at a constant current density of −0.4 mA cm −2 in 0.3 M CuSO4 (pH 9.5) under magnetic agitation. The composition and morphology of Cu/Cu2 O nanocomposites were characterized by X-ray diffraction, scanning electron microscopy, energy-dispersive spectroscopy and X-ray photoelectron spectroscopy. Taking advantage of the synergistic effects of Cu and Cu2 O, the fabricated Cu/Cu2 O/FTO electrode showed excellent electrocatalytic activity towards the oxidation of H2 O2 . The electrocatalytic performance of Cu/Cu2 O/FTO was evaluated by linear sweep voltammetry and amperometry. Under optimized conditions, the developed sensor exhibited a wide linear range of 0.2–2000 μM for the determination of H2 O2 with a detection limit of 0.04 μM (S/N = 3). In addition, the proposed H2 O2 sensor was successfully applied for the determination of H2 O2 in milk samples, indicating that the electrodeposited Cu/Cu2 O nanocomposites are promising nanomaterials for electrochemical sensors.